Management of technological innovation in companies - Tavera Colonna, Jazmín (2017)
Technological innovation face in our country more than a resource problem, is a management problem, which results in companies developing capabilities of investment, production and bonding. The development of these capabilities requires a strategy of technological innovation. For mexican metalworking and information technology sectors confirms the existence of a direct relationship between technology management and technological capabilities. Universities and colleges, such as Economy, have a role today unattended in these strategies.